Background information: $E_i$ is the parallel orthonormal frame along $c$ and $E_n=\nabla f\circ c$.

Lemma: Let $M$ be a Riemannian manifold and $f\in C^\infty(M)$ with $||\text{grad} f||=1$. If $c$ is an integral curve of $\text{grad}f$, then $c$ is a geodesic realizing the distance between any two of its points and

$$\begin{align} -\text{Ric}(\dot{c},\dot{c})&=(\Delta f\circ c)'+||\text{Hess}f\circ c||^2\\ &\geq (\Delta f\circ c)'+\frac{1}{n-1}(\Delta f\circ c)^2\\ \end{align} $$

where $\Delta f=\text{tr} \text{ Hess} f$.


enter image description here

This is a proof from Eschenburg and Heintze's paper, An Elementary Proof of the Cheeger-Gromoll Splitting theorem. Below are my questions and concerns. I would really appreciate it if someone could help me understand the steps. Thanks.

Question 1: Using Petersons' text it seems that $$||\text{Hess}f||^2=\sum_{i,j=1}^n\langle \nabla_{E_i}E_n,E_j\rangle^2$$ so I don't see how the author gets his computation from.

Question 2 I don't see why $-||\text{Hess}f||^2\leq- \sum_{i=1}^n\langle\text{Hess}f(E_i),E_i\rangle^2$

Question 3 I don't see how they get the inequality $-\sum_{i=1}^n\langle\text{Hess}f(E_i),E_i\rangle^2\leq -\frac{1}{n-1}(\Delta f)^2$.


Question 1 Given a function $f : M \to \mathbb R$ and $g$ a metric, the Hessian of $f$, $H = \text{Hess}_f$ is a $(1,1)$-tensor $TM \to TM$ defined as $$ \text{Hess}_f (X) =\nabla_X \nabla f.$$ For any $(1,1)$ tensor, one can define the norm $\|H\|$ to be $$\| H\|^2 = \sum_{i,j=1}^n \langle H(E_i), E_j\rangle^2,$$ where $\{E_1, E_2, \cdots, E_n\}$ is any orthonormal basis. Thus in our situation $$\|\text{Hess}_f\|^2 = \sum_{i,j=1}^n \langle \text{Hess}_f(E_i), E_j\rangle^2 = \sum_{i,j=1}^n \langle \nabla_{E_i} \nabla f , E_j\rangle^2 = \sum_{i,j=1}^n \langle \nabla_{E_i} E_n , E_j\rangle^2$$ as in our case $\nabla f = E_n$ along $c$.

Question 2 follows from the defintion: $$\begin{split} \|\text{Hess}_f\|^2 &= \sum_{i,j=1}^n \langle \text{Hess}_f(E_i) , E_j\rangle^2 \\ &\ge \sum_{i=1}^n \langle \text{Hess}_f (E_i), E_i\rangle^2. \end{split}$$

Question 3 Using $\Delta f = \text{tr}\text{Hess}_f$, $$\begin{split} (\Delta f)^2 &= (\text{tr} \text{Hess}_f)^2 \\ &= \left(\sum_{i=1}^n \langle\text{Hess}_f(E_i), E_i\rangle\right)^2 \\ &= \left(\sum_{i=1}^{n-1} \langle\text{Hess}_f(E_i), E_i\rangle\right)^2 \end{split}$$

since the last term is zero:
$$\langle \text{Hess}_f (E_n), E_n \rangle= \langle \nabla_{E_n} E_n,E_n\rangle =\frac 12 E_n \langle E_n, E_n\rangle = 0.$$

Now by Cauchy Schwarz inequality, $$\begin{split} (\Delta f)^2 &= \left(\sum_{i=1}^{n-1} \langle\text{Hess}_f(E_i), E_i\rangle\right)^2 \\ &\le \left(\sum_{i=1}^{n-1} 1^2 \right)\left(\sum_{i=1}^{n-1} \langle \text{Hess}_f (E_i), E_i\rangle^2 \right)\\ &= (n-1) \left(\sum_{i=1}^{n-1} \langle \text{Hess}_f (E_i), E_i\rangle^2 \right). \end{split}$$

  • $\begingroup$ Hi John, so your answer helps with everything except the jump the author makes from line 3 to line 4. His definition of the norm of the Hessian is different from what you and I defined. $\endgroup$ – Enigma Dec 1 '15 at 7:15
  • $\begingroup$ Can you state the definition that the authors used? @Enigma $\endgroup$ – user99914 Dec 1 '15 at 7:17
  • $\begingroup$ So the author basically says that $||\text{Hess}f||^2=\sum_{i,j=1}^n\langle \nabla_{E_i}E_n,E_j\rangle\langle\nabla_{E_j}E_n,E_i\rangle$, which doesn't seem to coincide with our defintion. This can be seen in the equality from line 3 to line 4 in the proof given by the author. $\endgroup$ – Enigma Dec 1 '15 at 7:30
  • 1
    $\begingroup$ That's because $\langle \text{Hess}_f (X), Y\rangle = \langle \text{Hess}_f (Y), X\rangle$ as $\langle \nabla_X \nabla f, Y\rangle = X(Yf ) - \langle \nabla f, \nabla _X Y\rangle$ (see the calculation here. @Enigma $\endgroup$ – user99914 Dec 1 '15 at 7:39

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.